Current Problems in the Theory of Legal Awareness and the Legal Culture of Young People - Urinboev Dilmurod Tura oglu (Genius Journals, 2022)
In this article the author analyses the issues of formation of legal consciousness and legal culture of young people, and consistently and contradictorily reveals different aspects of the formation of legal consciousness in the same category of the population, taking into account the specifics of this process.
Keywords: Legal culture; a legal culture of young people; young people; legal education